The Relationship Between the Use of Information Technology and Work Motivation on Work Productivity of Surakarta City Government Employees - Wiedy Rahmawati; Agus Suyatno; Esti Dwi Rahmawati (SMARTINDO, 2025)
Purpose - This study aims to examine the influence of information technology utilization and work motivation on the work productivity of civil servants at the Surakarta City Government. It emphasizes the importance of digital transformation and internal motivation in enhancing bureaucratic performance. Design/methodology/approach - This quantitative research employed a survey distributed to 100 respondents selected through cluster sampling across 10 government departments. Data were analyzed using Structural Equation Modeling (SEM-PLS) with the assistance of SmartPLS 4 software. Originality - This study contributes to the ongoing discourse on public sector digitalization by simultaneously assessing the relative influence of technology adoption and work motivation on productivity outcomes in a regional government setting. Findings and Discussion - The findings reveal that both variables significantly affect productivity. Work motivation had a stronger effect (coefficient = 0.751; p < 0.001) than information technology (coefficient = 0.154; p < 0.05). These results indicate that motivational factors are primary drivers of employee performance, while technology acts as a complementary enabler. Conclusion - The study suggests the need for dual-strategy implementation: strengthening internal motivation through supportive policies and improving technology adoption via training and user-centered design to optimize productivity gains in public services.